Staying in, nationality and residence of the requested person as grounds for optional non-execution of the European arrest warrant: the Portuguese case - Jorge Bheron Rocha (Revista Brasileira de Direito Processual Penal)
The purpose of this study is to investigate the grounds for optional non-execution of the European Arrest Warrant in the event that the requested person is staying in, or is a national or a resident in the State, in particular the Portuguese case. The research is important because the EAW is an instrument that seeks to bypass the disadvantages of extradition, seeking simplification and speed in face of the practical difficulties of prosecution in light of the free movement of people within the European Union territory. The Framework Decisions of the Council of the European Union, the relevant Portuguese legislation and the jurisprudence of the Portuguese Courts and the Court of Justice of the European Union are used as sources of analysis. Objective and subjective requirements, the limits of faculties, the outlines of the commitment assumed as a result of the refusal, the need for possible adaptation of the sentence in face of the apparent conflict between its immutability and the reserve of sovereignty of the Portuguese State, and the relationship of the institute with the principle of mutual recognition, which became the cornerstone of judicial cooperation within the European Union’s area of freedom, security and justice.